The principles and components of business models for sustainability - Turan, Ugur (Національний технічний університет "Харківський політехнічний інститут", 2020)
The article combines the key principles and components of business sustainability, highlights the specific features of the energy sector. Ukrainian small and medium-sized businesses have just begun to take their first tentative steps towards a completely different approach to creating and maintaining value, but this article concludes that there will be completely new perspectives for sustainable enterprise development along with new ways of creating and maintaining value. This article provides a theoretically grounded as well as a realistic account of how business model development can be an important component in the overall transition to sustainable development, going beyond the pursuit of innovative technologies. For the Kharkiv-focused small and medium-sized companies, which were developed by the author and worked with, sustainable development groups were formed and the important order of the indicators of these groups was sent to the companies as a survey study. In addition, a mechanism by which SMEs can adopt the Energy 4.0 approach in line with the modernization and innovative structure of the energy sector and the energy targets of Ukraine has been presented to their organizations. The author proposed a Sustainable Development Association, where SMEs will supervise and consult all these digitalization and innovation processes in line with their sustainable development goals. This association has been planned as a joint structure for the development of existing SMEs in the entire energy sector. As a result of the study, the basic components of the organizational mechanism were identified. The main elements are characterized and their content is revealed. It has been observed that the majority of the feedback received from the companies has a positive intention and adopts an energy 4.0 understanding. The presence of the relevant components of the mechanism in small and medium-sized businesses is revealed. With the growing understanding that innovative technologies alone are not enough to make sustainable growth a reality, the article focuses on the need to find and create radically new business models.

У статті об'єднані ключові принципи і складові стійкості бізнесу, висвітлено особливості енергетичного сектору. Робиться висновок про те, що з’являються нові перспективи для сталого розвитку підприємств поряд з новими способами створення і підтримки їх виробничої функції. У дослідженні наводиться теоретично обгрунтований, а також реалістичний погляд на необхідність розробки бізнес-моделі як важливої компоненти загального переходу до сталого розвитку, який стає ширшим ніж впровадження інноваційних технологій. Для українських малих і середніх підприємств (МСП), які досліджував автор, були сформовані групи сталого розвитку, і визначена послідовність показників цих груп. У зв'язку з усвідомленням того, що застосування одних інноваційних технологій недостатньо для забезпечення сталого розвитку, в статті робиться акцент на необхідність пошуку і створення радикально нових бізнес-моделей.
Принципи та компоненти бізнес моделей сталого розвитку
Keywords: sustainable business; digitalization; organizational structure; sustainable development; small and medium-sized enterprises; сталий бізнес; дігіталізація; організаційна структура; сталий розвиток; малі та середні підприємства